Effect of Low-level Laser Therapy and Platelet-rich Fibrin on the Treatment of Intra-bony Defects - Bala Raja Thalaimalai, Devi; John Victor, Dhayanand; Prakash, Ponnudurai Samuel Ganana; Subramaniam, Sangeetha; Cholan, Priyanka K (Journal of Lasers in Medical Sciences, 2020)
Introduction: Attempts to regenerate the periodontal osseous defect, which is lost as a result of periodontal disease, require the tapping of the innate healing potential of periodontium through appropriately designed therapeutic strategies. A multitude of grafted and non-grafted approaches have been used in the management of Intra-bony defects. However, they do not provide predictable periodontal regeneration. The aim of this study was to evaluate the combined effect of low-level laser therapy (LLLT) and platelet-rich fibrin (PRF), in site modulated intra-bony defects (decortication), which were accessed using a simplified papilla preservation flap (SPPF), on the clinical and radiographic outcomes of periodontal disease. Methods: A total of 30 patients with intra-bony defects were recruited for the study and randomly distributed in two groups (n=15). Test group sites were accessed with SPPF and the defects received intra-marrow Penetration (IMP) following debridement and were irradiated with a low-level laser followed by PRF grafting and suturing done. The control group defects were accessed with SPPF and grafted with PRF before being secured by sutures. The plaque and bleeding score, PPD, CAL, and the position of the gingival margin with radiographic defect depth were recorded and analyzed at baseline and six months post-intervention using the student’s t-test and Wilcoxon signed-rank test. Results: The test group showed a clinically relevant increase in mean PPD reduction, CAL gain, and radiographic bone fill (3.6 ± 1.35 mm, 3.26 ± 1.16 mm, and 2.44 ± 1.24 mm) compared to the control group (2.93 ±1.1 mm, 2.267 ± 1.33 mm and 1.26 ± 0.99 mm) six months post-intervention. However, intergroup comparison between the test and control groups did not show any statistically significant difference. Conclusion: These results highlight that test protocol had greater amelioration of the effects of periodontal disease and all the investigated clinical and radiographic parameters showed considerable improvement from baseline to 6 months within the test and control group, but intergroup comparison between the test and control groups did not show any statistically significant difference, indicating statistical equivalence between the test and control protocol.